Accuracy and limitations of diagnostic methods for avascular necrosis of the hip. (March 2013) - Karantanas, Apostolos H
<x xml:space="preserve">Abstract</x> Introduction: Femoral head avascular necrosis (FHAVN) is the result of irreversible anoxia of the subchondral bone. The death of bone cells can cause articular collapse and pain, and in turn usually leads to degenerative arthritis. FHAVN is a common disorder, affecting mainly young male adults. Reliability, accuracy and prognostic value of any classification system are important in evaluation and treatment of FHAVN. Areas covered: Although in the past, scintigraphy and CT and more recently PET have been used for diagnosing AVN, currently the most important imaging methods included in the most widely used classification systems, consist of radiographs and magnetic resonance imaging (MRI). The latter is used in major classification systems for early detection (pre-radiographic stage) of FHAVN and for assessing lesion size and location before collapse of the articular surface occurs. The purpose of this review is to present the current data regarding the accuracy of the X-rays and MRI in diagnosing, monitoring and postoperative evaluation of FHAVN. Expert opinion: The author's opinion is that MRI may contribute to improve staging, investigate radiologically occult collapse, depict other causes of disability and pain, assess prognosis and evaluate treatment. Newer MRI techniques, such as diffusion-weighted imaging and perfusion imaging, have not yet provided additional and clinically useful information.